2013
DOI: 10.1111/codi.12446
|View full text |Cite
|
Sign up to set email alerts
|

First report: robotic pelvic exenteration for locally advanced rectal cancer

Abstract: This the first report of the use of the da Vinci robotic system for pelvic exenteration in patients with locally advanced rectal cancer invading the prostate and seminal vesicles. The robot may have a potential role in selected patients requiring exenterative pelvic surgery particularly in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Video demonstrates our standardized technique of TPE, using the da Vinci Xi robotic platform, after neoadjuvant chemoradiation in a patient with locally advanced rectal cancer. The surgical duration and blood loss are in line with other reported series on robotic rectal cancer exenterative surgeries.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Video demonstrates our standardized technique of TPE, using the da Vinci Xi robotic platform, after neoadjuvant chemoradiation in a patient with locally advanced rectal cancer. The surgical duration and blood loss are in line with other reported series on robotic rectal cancer exenterative surgeries.…”
supporting
confidence: 88%
“…Robotic TPE for rectal cancer was shown to be feasible technically in 2014 on a daVinci Si platform . Compared with laparoscopy, robotic surgery removes dependence on an assistant for vision and affords excellent dexterity, and the three‐dimensional (3D) platform provides an unparalleled advantage to work in a narrow male pelvis.…”
mentioning
confidence: 99%
“…One of the first reports of robotic pelvic exenteration for locally advanced rectal cancer come from Shin et al [44] . They described three cases including two extended resections with en bloc prostatectomy and intracorporeal vesicourethral anastomosis, and one total pelvic exenteration with intracorporeal ileal conduit.…”
Section: Ogura Et Almentioning
confidence: 99%
“…The preliminary data have shown minimal blood loss, short hospital stays, low morbidity rates, and non-comprising short-term oncological outcome. The first report of robotic PE in advanced rectal cancer patients was published by Shin et al[24] in 2014. The authors reported on 3 consecutive male patients with locally advanced rectal cancer involving prostate and seminal vesicles.…”
Section: Discussionmentioning
confidence: 99%